VALUES OF CIVIL SOCIETY: FEATURES OF THE PROCESS OF FORMATION IN THE SYSTEM OF CIVIL RELATIONS - Климончук, В. Й. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The peculiarities of the formation of values in the system of civil relations are studied. The author's vision is based on the definition of a system of values through an analysis of the ways, conditions of self-realization, self-determination, self-realization of the civil system, in which the relations of internal and external character in a certain way are coordinated. Characterized by a system of values of a political and civil character that allows one to determine the main contradiction of formation and affirmation in the new political circumstances that have developed in modern Ukraine, the essence of which is the transition from the values ​​of abstract to concrete, meaningful and real: cost of life, individual freedom, property, forms and methods of self-government, etc.